Research on Lightweight Rail Vehicle Body Based on Sensitivity Analysis - Yin, Jian; Zhang, Qingchao; Li, Xianglong; Zhu, Yaoyao; Liu, Ziyuan; Liu, Yu; Sha, Zhihua (Journal of Engineering and Technological Sciences, 2024)
In view of the development trend of rail vehicles towards higher operating speed and low power consumption, a scheme for a lightweight rail vehicle body is proposed, based on sensitivity analysis. Using topology optimization of the vehicle body section structure, finite element models of the vehicle body section structure under single working conditions and multiple working conditions were established, respectively, and the force transmission path of the vehicle body structure under different working conditions was obtained under different working conditions. The topology of the cross-sectional structure of the vehicle body was optimized by the compromise planning method with weights. Then, a reconstruction and performance analysis of the car body section was carried out based on the optimization results and finally the finite difference method was used to analyze the sensitivity of the vehicle body structure and the vehicle body size was optimized based on the sensitivity analysis results. The results showed that the weight reduction rate of the railway vehicle body section stiffened plate was 4.47% compared to the optimization period and the modal performance analysis results of the optimized structure met the requirements. The weight reduction ratio of the optimized body structure was 21.6%